Acral Lentiginous Melanoma Presenting with Amelanotic Metastasis - Alaka J Mohan; AjithkumarKidanga zhiyathmana; Neelakandhan Asokan (Clinical Dermatology Review)
Acral melanoma is an aggressive subtype of melanoma which presents on palms soles and nails. It is more frequently seen in patients with Asian or African descent. It usually presents at an advanced stage due to a lack of patient awareness and diagnostic delay. Here, we report a case of an elderly male who presented with unusual nodules on the upper limb.